Tiktok Sebagai Media Interaktif Pembelajaran Editing Video - Wibi Ardi Alvianto; Juni Amanullah; Lukman Santoso (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
The social media platform TikTok has grown rapidly as one of the main platforms for creative expression and information exchange. This article discusses the use of video editing tools provided by TikTok in creating interesting learning materials for students. We analyze TikTok's creative features including visual effects, music, and quick edits, and illustrate how to apply them to learning. This research involves a qualitative approach through case studies, focusing on the teacher's experience in creating learning materials with the TikTok video editing tool. The findings show that this approach can motivate students by providing visual content that matches the preferences of the younger generation. Students' positive response to this approach indicates increased engagement and interest in learning. However, challenges in utilizing TikTok's video editing tools are also acknowledged. Integrating creativity with substantial content and ensuring the integrity of education is maintained are some of the aspects that must be considered. Ethical and privacy implications are also discussed in the context of the use of social media platforms in education. In conclusion, TikTok's video editing tools offer exciting potential for creating impactful learning materials. With a thoughtful approach, educators can design content that fits current visual trends and communication styles, while maintaining the required educational quality.